MoS2 (at) RGO composite material and preparation method thereof
The preparation of MoS2@RGO composite material by one-step hydrothermal method solves the problems of low wave absorption performance and narrow absorption bandwidth of composite materials in the prior art, and realizes the combination of high wave absorption performance and wide bandwidth, which is suitable for the application of electromagnetic wave absorption materials. .
Patent Information
- Application Number
- CN202411283936.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-13
- Publication Date
- 2024-12-20
AI Technical Summary
In the prior art, the composite materials have low wave absorption performance and narrow absorption bandwidth, which cannot meet the needs of electromagnetic interference and radiation in 5G technology and electronic equipment.
MoS2@RGO composite material was prepared by one-step hydrothermal method, graphene oxide sheets were prepared by Hummers method, and evenly mixed with MoS2 powder under hydrothermal conditions, and then uniformly mixed with paraffin to press into a coaxial ring to realize MoS2@RGO composite material Preparation.
The combination of high absorbance performance and wide effective absorption bandwidth is achieved, which simplifies the preparation process and reduces production costs, and is suitable for the application of electromagnetic wave absorbing materials.
Smart Images

Figure CN119171089A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of composite material preparation, and in particular relates to a method for preparing a MoS2@RGO composite material, and also relates to the MoS2@RGO composite material. Background Art
[0002] With the development of 5G technology and the widespread use of electronic devices, electromagnetic interference and radiation problems are becoming increasingly serious, posing a serious radiation threat to human health and information security. Therefore, there is an urgent need to develop new high-performance electromagnetic wave absorbing (MA) materials with strong absorption, large bandwidth, small thickness, low density, and high temperature / corrosion resistance.
[0003] However, the use of single components and traditional absorption materials is not enough to meet social and industrial requirements. Transition metal dichalcogenides (TMDs) have attracted increasing interest in the field of MA due to their unique layered structure, semiconductor or superconducting properties, and rich phase composition. Among them, the unique flower-like structure of molybdenum disulfide (MoS2) is not only conducive to the multiple reflections of the incident electromagnetic waves, but also has a large specific surface area, which is conducive to the construction of heterogeneous interfaces and promotes interface polarization. In addition, its high chemical stability and high surface activation energy make it an ideal candidate for absorbing materials. However, its low electrical conductivity may not achieve the most appropriate impedance matching, and it is difficult to achieve satisfactory microwave absorption performance without coupling with other dielectric or magnetic elements. Carbon materials such as reduced graphene oxide (rGO) have high specific surface area, good conductivity, high chemical stability, low density, and high complex dielectric constant. Therefore, it has broad application prospects to combine it with MoS2 to form electromagnetic wave absorbing materials. Existing preparation methods include chemical vapor deposition, solution self-assembly, solvent thermal intercalation ultrasonic stripping, and γ-ray irradiation reduction, but they have high requirements for experimental equipment and difficult to control reaction conditions. The one-step hydrothermal method can be used to make MoS2@RGO composite materials after washing and drying. It is not only simple to operate, but also can obtain high-quality products at a lower cost, and has great application potential. Summary of the invention
[0004] The purpose of the present invention is to provide a method for preparing a MoS2@RGO composite material, which solves the problems of low wave absorption performance and narrow absorption bandwidth of the composite material in the prior art.
[0005] Another object of the present invention is to provide a MoS2@RGO composite material.
[0006] The technical solution adopted by the present invention is a method for preparing a MoS2@RGO composite material, which is specifically implemented according to the following steps:
[0007] Step 1, preparing graphene oxide sheets by Hummers method;
[0008] Step 2, preparing MoS2@RGO powder by hydrothermal method;
[0009] Step 3, uniformly mixing the MoS2@RGO powder obtained in step 2 with molten paraffin, and then putting the mixture into a mold and pressing it into a coaxial ring to obtain a MoS2@RGO composite material.
[0010] The present invention is also characterized in that:
[0011] In step 1, specifically:
[0012] Step 1.1, dissolving graphene in concentrated sulfuric acid in an oil bath at 80°C, then slowly adding phosphorus pentoxide and potassium persulfate, stirring for 6-12 hours to obtain a mixture; dispersing the obtained mixture in deionized water and filtering it by suction, adding the precipitate obtained by filtering to concentrated sulfuric acid in an ice bath, stirring evenly, and then adding K2Mn2O4 three times, stirring for 10 minutes each time after adding, to obtain a solution;
[0013] Step 1.2, under water bath conditions, adding deionized water and hydrogen peroxide dropwise to the solution obtained in step 1.1 with stirring to obtain a graphene oxide solution;
[0014] Step 1.3, add the graphene oxide solution obtained in step 1.2 to dilute hydrochloric acid, let it stand for 12 hours, then pour out the upper layer of acid, and then put the lower layer of solution into a dialysis bag and dialyze for 2 days. Change the water after one day of dialysis. After the dialysis is completed, stir the solution for 3-5 hours, pre-cool the obtained graphene oxide dispersion, and finally freeze-dry it to obtain graphene oxide sheets GO.
[0015] In step 1.1, the mass ratio of graphene, concentrated sulfuric acid, phosphorus pentoxide, potassium persulfate and K2Mn2O4 is 3:120:4:4:9.
[0016] In step 1.3, the precooling temperature is -22 to -26°C, and the precooling time is 2 to 8 hours; the freeze-drying temperature is -30 to -35°C, and the freeze-drying time is 48 to 72 hours.
[0017] In step 2, specifically:
[0018] GO was dissolved in deionized water, Na2Mo2O4·2H2O and TAA were added, and stirred for 20-30 min under ultrasonic conditions to make it uniformly dispersed, and then N2H4·H2O was added and mixed evenly. The mixture was then transferred to an autoclave for hydrothermal reaction and cooled to room temperature. The precipitate was collected, washed and dried to obtain MoS2@RGO powder.
[0019] The mass ratio of GO, Na2Mo2O4·2H2O, TAA, N2H4·H2O and deionized water is 0.19-0.38: 0.29-0.58: 0.21-0.42: 2: 75; the reaction temperature is 200℃, and the reaction time is 24h.
[0020] The melting temperature of paraffin is 60-80°C, the melting time is 10-20 min, and the mass ratio of MoS2@RGO powder to paraffin is 1:4.
[0021] Another technical solution adopted by the present invention is the MoS2@RGO composite material prepared by the preparation method of the MoS2@RGO composite material.
[0022] The beneficial effects of the present invention are as follows: the method of the present invention, through the compounding of RGO and MoS2, makes it uniformly deposited on the surface of the RGO sheet, realizes a controllable dielectric constant and excellent electromagnetic properties, and at the same time combines excellent impedance matching with moderate attenuation capability, exhibits excellent EMW attenuation capability, and prepares a composite material with high wave absorption performance and wide effective absorption bandwidth; and the preparation method is simple and feasible, has a low production cost, and is easy to mass produce. BRIEF DESCRIPTION OF THE DRAWINGS
[0023] Figure 1 is a reflection loss diagram of the MoS2@RGO composite material prepared in Examples 1-3 of the present invention;
[0024] Figure 2 It is the EAB diagram of the MoS2@RGO composite material prepared in Examples 1-3 of the present invention. DETAILED DESCRIPTION
[0025] The present invention is described in detail below with reference to the accompanying drawings and specific embodiments.
[0026] The preparation method of the MoS2@RGO composite material of the present invention is specifically implemented according to the following steps:
[0027] Step 1, preparing graphene oxide sheets by Hummers method; specifically:
[0028] Step 1.1, dissolving graphene in concentrated sulfuric acid in an oil bath at 80°C, then slowly adding phosphorus pentoxide (P2O5) and potassium persulfate (K2S2O8), stirring for 6-12 hours to obtain a mixture; dispersing the obtained mixture in deionized water and filtering it by suction, adding the precipitate obtained by filtering into concentrated sulfuric acid in an ice bath, stirring evenly, and then adding K2Mn2O4 three times, stirring for 10 minutes each time after adding, so that oxidation occurs between graphite layers and the solution gradually turns green;
[0029] The graphene manufacturer is Alfa Aesar (China) Chemicals Co., Ltd., with a purity of 99.8% and a particle size of 325 mesh;
[0030] The mass ratio of graphene, concentrated sulfuric acid, phosphorus pentoxide, potassium persulfate and K2Mn2O4 is 3:120:4:4:9;
[0031] Step 1.2, under water bath conditions, deionized water and hydrogen peroxide (H2O2) are added dropwise to the solution obtained in step 1.1 with stirring to terminate the reaction, thereby obtaining a graphene oxide solution, which becomes a yellow liquid with a metallic luster;
[0032] The water bath temperature is 32-38°C and the stirring time is 2h;
[0033] Step 1.3, adding the graphene oxide solution obtained in step 1.2 to dilute hydrochloric acid, standing for 12 hours, then pouring off the upper acid layer, and then putting the lower solution into a dialysis bag, dialyzing for 2 days, changing the water once after one day of dialysis, stirring the solution for 3-5 hours after the dialysis, precooling the obtained graphene oxide dispersion at -22 to -26 ° C for 2-8 hours, and finally freeze-drying to obtain graphene oxide sheets (GO);
[0034] The freeze drying temperature is -30 to -35°C and the freeze drying time is 48 to 72 hours;
[0035] Step 2, preparing MoS2@RGO powder by hydrothermal method;
[0036] Specifically, GO was dissolved in deionized water, sodium molybdate (Na2Mo2O4·2H2O) and thioacetamide (TAA, C2H5NS) were added, and the mixture was stirred for 20-30 min under ultrasonic conditions to make it uniformly dispersed, and then hydrazine hydrate (N2H4·H2O) was added and mixed evenly, and then the mixture was transferred to an autoclave for hydrothermal reaction at a reaction temperature of 200°C for a reaction time of 24 h, and then cooled to room temperature, and the precipitate was collected, washed, and dried to obtain MoS2@RGO powder;
[0037] The mass ratio of GO, Na2Mo2O4·2H2O, TAA, N2H4·H2O, and deionized water is 0.19-0.38: 0.29-0.58: 0.21-0.42: 2: 75;
[0038] Step 3, uniformly mixing the MoS2@RGO powder obtained in step 2 with molten paraffin, and then putting the mixture into a mold and pressing it into a coaxial ring to obtain a MoS2@RGO composite material;
[0039] The melting temperature of paraffin wax is 60-80°C, the time is 10-20 minutes, and the thickness of the coaxial ring is less than 0.30 cm;
[0040] The mass ratio of MoS2@RGO powder to paraffin is 1:4.
[0041] The mechanism of action of the method of the present invention is as follows: the composite of MoS2 and RGO optimizes the impedance matching, making it easy for electromagnetic waves to enter the interior of the material. Subsequently, the incident electromagnetic wave undergoes multiple reflections and scatterings on the flower-shaped molybdenum disulfide surface, thereby attenuating the incident wave. In addition, due to the composite of MoS2 and RGO, a large number of effective interfaces are obtained, which triggers interface polarization and dipole polarization, improves dielectric loss, and further produces a stronger electromagnetic wave loss capacity, thereby obtaining a relatively excellent wave absorbing performance.
[0042] Example 1
[0043] The preparation method of the MoS2@RGO composite material of the present invention comprises the following specific steps:
[0044] Step 1, preparing graphene oxide sheets by Hummers method; specifically:
[0045] Step 1.1, in an oil bath at 80°C, dissolve 3g of graphene in 12mL of concentrated sulfuric acid, slowly add 4g of P2O5 and 4g of K2S2O8, and stir for 6h to obtain a mixture; disperse the obtained mixture in deionized water and filter it by suction, add the precipitate obtained by filtration into concentrated sulfuric acid under ice bath conditions, stir evenly, and then add K2Mn2O4 three times, stirring for 10min each time after adding, so that oxidation occurs between graphite layers and the solution gradually turns green;
[0046] The mass ratio of graphene, concentrated sulfuric acid, phosphorus pentoxide, potassium persulfate and K2Mn2O4 is 3:120:4:4:9;
[0047] Step 1.2, under water bath conditions, deionized water and hydrogen peroxide (H2O2) are added dropwise to the solution obtained in step 1.1 with stirring to terminate the reaction and obtain a graphene oxide solution, which becomes a yellow liquid with a metallic luster; the water bath temperature is 35° C., and the stirring time is 2 h;
[0048] Step 1.3, adding the graphene oxide solution obtained in step 1.2 to dilute hydrochloric acid, standing for 12 hours, then pouring off the upper acid layer, and then putting the lower solution into a dialysis bag, dialyzing for 2 days, changing the water once after one day of dialysis, stirring the solution for 3-5 hours after the dialysis, precooling the obtained graphene oxide dispersion at -26°C for 6 hours, and finally freeze-drying to obtain graphene oxide sheets (GO);
[0049] The freeze drying temperature is -35°C and the freeze drying time is 48h;
[0050] Step 2, preparing MoS2@RGO powder by hydrothermal method;
[0051] Specifically, GO was dissolved in deionized water, sodium molybdate (Na2Mo2O4·2H2O) and thioacetamide (TAA, C2H5NS) were added, and the mixture was stirred for 20 min under ultrasonic conditions to make it uniformly dispersed, and then hydrazine hydrate (N2H4·H2O) was added and mixed evenly, and then the mixture was transferred to an autoclave for hydrothermal reaction at a reaction temperature of 200°C for a reaction time of 24 h, and then cooled to room temperature, and the precipitate was collected, washed, and dried to obtain MoS2@RGO powder;
[0052] The mass ratio of GO, Na2Mo2O4·2H2O, TAA, N2H4·H2O, and water is 0.19:0.58:0.42:2:75;
[0053] Step 3, the MoS2@RGO powder obtained in step 2 is uniformly mixed with molten paraffin, and the mixture is then put into a mold (Φout=7.00mm and Φin=3.04mm) to make a coaxial ring; the melting temperature of the paraffin is 80°C, the time is 20min, and the thickness of the coaxial ring is 0.20cm; the mass ratio of MoS2@RGO powder to paraffin is 1:4;
[0054] Compared with commercial electromagnetic shielding materials (20 dB), the reflection loss of the MoS2@RGO composite material prepared in Example 1 is -31.50 dB, which is a corresponding increase of 57.5%.
[0055] Example 2
[0056] The preparation method of the MoS2@RGO composite material of the present invention comprises the following specific steps:
[0057] Step 1, preparing graphene oxide sheets by Hummers method; specifically:
[0058] Step 1.1, in an oil bath at 80°C, dissolve 3g of graphene in 12mL of concentrated sulfuric acid, slowly add 4g of P2O5 and 4g of K2S2O8, and stir for 6h to obtain a mixture; disperse the obtained mixture in deionized water and filter it by suction, add the precipitate obtained by filtration into concentrated sulfuric acid under ice bath conditions, stir evenly, and then add K2Mn2O4 three times, stirring for 10min each time after adding, so that oxidation occurs between graphite layers and the solution gradually turns green;
[0059] The mass ratio of graphene, concentrated sulfuric acid, phosphorus pentoxide, potassium persulfate and K2Mn2O4 is 3:120:4:4:9;
[0060] Step 1.2, under water bath conditions, deionized water and hydrogen peroxide (H2O2) are added dropwise to the solution obtained in step 1.1 with stirring to terminate the reaction and obtain a graphene oxide solution, which becomes a yellow liquid with a metallic luster; the water bath temperature is 35° C., and the stirring time is 2 h;
[0061] Step 1.3, adding the graphene oxide solution obtained in step 1.2 to dilute hydrochloric acid, standing for 12 hours, then pouring off the upper acid layer, and then putting the lower solution into a dialysis bag, dialyzing for 2 days, changing the water once after one day of dialysis, stirring the solution for 3-5 hours after the dialysis, precooling the obtained graphene oxide dispersion at -26°C for 6 hours, and finally freeze-drying to obtain graphene oxide sheets (GO);
[0062] The freeze drying temperature is -35°C and the freeze drying time is 48h;
[0063] Step 2, preparing MoS2@RGO powder by hydrothermal method;
[0064] Specifically, GO was dissolved in deionized water, sodium molybdate (Na2Mo2O4·2H2O) and thioacetamide (TAA, C2H5NS) were added, and the mixture was stirred for 20 min under ultrasonic conditions to make it uniformly dispersed, and then hydrazine hydrate (N2H4·H2O) was added and mixed evenly, and then the mixture was transferred to an autoclave for hydrothermal reaction at a reaction temperature of 200°C for a reaction time of 24 h, and then cooled to room temperature, and the precipitate was collected, washed, and dried to obtain MoS2@RGO powder;
[0065] The mass ratio of GO, Na2Mo2O4·2H2O, TAA, N2H4·H2O, and water is 0.19:0.29:0.21:2:75;
[0066] Step 3, the MoS2@RGO powder obtained in step 2 is uniformly mixed with molten paraffin, and the mixture is then placed in a special mold (Φout=7.00mm and Φin=3.04mm) to form a coaxial ring; the melting temperature of the paraffin is 80°C, the time is 20min, and the thickness of the coaxial ring is 0.25cm; the mass ratio of MoS2@RGO powder to paraffin is 1:4;
[0067] Compared with commercial electromagnetic shielding materials (20 dB), the reflection loss of the MoS2@RGO composite material prepared in Example 2 is -58.20 dB, which is a corresponding increase of 191%.
[0068] Example 3
[0069] The preparation method of the MoS2@RGO composite material of the present invention comprises the following specific steps:
[0070] Step 1, preparing graphene oxide sheets by Hummers method; specifically:
[0071] Step 1.1, in an oil bath at 80°C, dissolve 3g of graphene in 12mL of concentrated sulfuric acid, slowly add 4g of P2O5 and 4g of K2S2O8, and stir for 6h to obtain a mixture; disperse the obtained mixture in deionized water and filter it by suction, add the precipitate obtained by filtration into concentrated sulfuric acid under ice bath conditions, stir evenly, and then add K2Mn2O4 three times, stirring for 10min each time after adding, so that oxidation occurs between graphite layers and the solution gradually turns green;
[0072] The mass ratio of graphene, concentrated sulfuric acid, phosphorus pentoxide, potassium persulfate and K2Mn2O4 is 3:120:4:4:9;
[0073] Step 1.2, under water bath conditions, deionized water and hydrogen peroxide (H2O2) are added dropwise to the solution obtained in step 1.1 with stirring to terminate the reaction and obtain a graphene oxide solution, which becomes a yellow liquid with a metallic luster; the water bath temperature is 35° C., and the stirring time is 2 h;
[0074] Step 1.3, adding the graphene oxide solution obtained in step 1.2 to dilute hydrochloric acid, standing for 12 hours, then pouring off the upper acid layer, and then putting the lower solution into a dialysis bag, dialyzing for 2 days, changing the water once after one day of dialysis, stirring the solution for 3-5 hours after the dialysis, precooling the obtained graphene oxide dispersion at -26°C for 6 hours, and finally freeze-drying to obtain graphene oxide sheets (GO);
[0075] The freeze drying temperature is -35°C and the freeze drying time is 48h;
[0076] Step 2, preparing MoS2@RGO powder by hydrothermal method;
[0077] Specifically, GO was dissolved in deionized water, sodium molybdate (Na2Mo2O4·2H2O) and thioacetamide (TAA, C2H5NS) were added, and the mixture was stirred for 20 min under ultrasonic conditions to make it uniformly dispersed, and then hydrazine hydrate (N2H4·H2O) was added and mixed evenly, and then the mixture was transferred to an autoclave for hydrothermal reaction at a reaction temperature of 200°C for a reaction time of 24 h, and then cooled to room temperature, and the precipitate was collected, washed, and dried to obtain MoS2@RGO powder;
[0078] The mass ratio of GO, Na2Mo2O4·2H2O, TAA, N2H4·H2O, and water is 0.38:0.29:0.21:2:75;
[0079] Step 3, the MoS2@RGO powder obtained in step 2 is uniformly mixed with molten paraffin, and the mixture is then placed in a special mold (Φout=7.00mm and Φin=3.04mm) to form a coaxial ring; the melting temperature of the paraffin is 80°C, the time is 20min, and the thickness of the coaxial ring is 0.10cm; the mass ratio of MoS2@RGO powder to paraffin is 1:4;
[0080] Compared with commercial electromagnetic shielding materials (20 dB), the reflection loss of the MoS2@RGO composite material prepared in Example 3 is -37.00 dB, which is correspondingly increased by 85%.
[0081] The reflection loss diagram of the MoS2@RGO composite material prepared at different ratios in Examples 1-3 of the present invention is as follows: Figure 1 As shown, with the decrease of the content in MoS2, the reflection loss first decreases and then increases; Figure 2 The EAB diagrams of composite materials at different proportions show that the materials of Examples 1-3 all have small reflection losses, all <-30 dB, and wide effective absorption bandwidths, showing excellent wave absorbing performance.
[0082] The MoS2@RGO composite material prepared by the method of the present invention combines the unique flower-like structure of MoS2 and the high complex dielectric constant of RGO, improves impedance matching, makes it easier for electromagnetic waves to enter, and multiple reflections and scattering occur in the flower-like structure. The incident wave is attenuated by the interface polarization and dipole polarization induced by a large number of effective interfaces, thereby obtaining excellent wave absorbing performance. When the composite material prepared in Example 2 has a MoS2:RGO ratio of 1:1 and a filling ratio of 20%, the reflection loss is -58.20dB and the effective absorption bandwidth is 5.17GHz. This provides a feasible solution for making wave absorbing materials with strong absorption and large bandwidth.
[0083] The preparation method of the MoS2@RGO composite material of the present invention utilizes freeze drying and hydrothermal method to prepare the MoS2@RGO composite material with high-efficiency electromagnetic shielding performance. The preparation process is safe and environmentally friendly, the preparation process is simple and the cost is low, and it has wide practicality and promotion value. The MoS2@RGO composite material prepared by the preparation method of the present invention has excellent electromagnetic shielding performance and can meet the application requirements of aerospace, electronic packaging and other fields.
Claims
1. A method for preparing a MoS2@RGO composite material, characterized in that: Follow the steps below to implement it: Step 1, preparing graphene oxide sheets by Hummers method; Step 2, preparing MoS2@RGO powder by hydrothermal method; Step 3, evenly mix the MoS2@RGO powder obtained in step 2 with molten paraffin, and then put the mixture into a mold and press it into a coaxial ring to obtain a MoS2@RGO composite material.
2. The method for preparing the MoS2@RGO composite material according to claim 1, characterized in that: In the step 1, specifically: Step 1.1, dissolving graphene in concentrated sulfuric acid in an oil bath at 80°C, then slowly adding phosphorus pentoxide and potassium persulfate, stirring for 6-12 hours to obtain a mixture; dispersing the obtained mixture in deionized water and filtering it by suction, adding the precipitate obtained by filtering to concentrated sulfuric acid in an ice bath, stirring evenly, and then adding K2Mn2O4 three times, stirring for 10 minutes each time after adding, to obtain a solution; Step 1.2, under water bath conditions, adding deionized water and hydrogen peroxide dropwise to the solution obtained in step 1.1 with stirring to obtain a graphene oxide solution; Step 1.3, add the graphene oxide solution obtained in step 1.2 to dilute hydrochloric acid, let it stand for 12 hours, then pour out the upper layer of acid, and then put the lower layer of solution into a dialysis bag and dialyze for 2 days. Change the water after one day of dialysis. After the dialysis is completed, stir the solution for 3-5 hours, pre-cool the obtained graphene oxide dispersion, and finally freeze-dry it to obtain graphene oxide sheets GO.
3. The method for preparing the MoS2@RGO composite material according to claim 2, characterized in that: In the step 1.1, the mass ratio of graphene, concentrated sulfuric acid, phosphorus pentoxide, potassium persulfate and K2Mn2O4 is 3:120:4:4:
9.
4. The method for preparing the MoS2@RGO composite material according to claim 2, characterized in that: In the step 1.3, the precooling temperature is -22 to -26°C, and the precooling time is 2 to 8 hours; the freeze-drying temperature is -30 to -35°C, and the freeze-drying time is 48 to 72 hours.
5. The method for preparing the MoS2@RGO composite material according to claim 1, characterized in that: In the step 2, specifically: GO was dissolved in deionized water, Na2Mo2O4·2H2O and TAA were added, and stirred for 20-30 min under ultrasonic conditions to make it uniformly dispersed, and then N2H4·H2O was added and mixed evenly. The mixture was then transferred to an autoclave for hydrothermal reaction and cooled to room temperature. The precipitate was collected, washed and dried to obtain MoS2@RGO powder.
6. The method for preparing the MoS2@RGO composite material according to claim 5, characterized in that: The mass ratio of GO, Na2Mo2O4·2H2O, TAA, N2H4·H2O and deionized water is 0.19-0.38: 0.29-0.58: 0.21-0.42: 2: 75; the reaction temperature is 200℃, and the reaction time is 24h.
7. The method for preparing the MoS2@RGO composite material according to claim 1, characterized in that: In the step 3, the melting temperature of the paraffin is 60-80°C, the melting time is 10-20 min, and the mass ratio of MoS2@RGO powder to paraffin is 1:
4.
8. The MoS2@RGO composite material prepared by the preparation method of the MoS2@RGO composite material according to any one of claims 1 to 7.
